How pure are your vesicles?. Issue 1 (14th January 2013) - Webber, Jason; Clayton, Aled
Abstract : We propose a straightforward method to estimate the purity of vesicle preparations by comparing the ratio of nano‐vesicle counts to protein concentration, using tools such as the increasingly available NanoSight platform and a colorimetric protein assay such as the BCA‐assay. Such an approach is simple enough to apply to every vesicle preparation within a given laboratory, assisting researchers as a routine quality control step. Also, the approach may aid in comparing/standardising vesicle purity across diverse studies, and may be of particular importance in evaluating vesicular biomarkers. We herein propose some criteria to aid in the definition of pure vesicles.